Evolution of vegetation phenology research under climate change: a comprehensive bibliometric study - Zhou, Ruiwu; Wen, Guojing; Li, Hanqi; Zhu, Sisi; Li, Yundan; Wang, Xinyi (Frontiers in Forests and Global Change, 2025)
IntroductionVegetation phenology serves as a sensitive indicator of terrestrial ecosystem responses to climate change. Over the past few decades, research on phenological changes, especially in forest ecosystems, has expanded substantially.MethodsThis study conducts a systematic bibliometric analysis of global literature on vegetation phenology and climate change from 1995 to 2024, based on 599 publications retrieved from the Web of Science Core Collection and Scopus. Using VOSviewer, CiteSpace, Bibliometrix (R package), and SciMAT, we examined publication trends, geographic distribution, institutional collaboration, author contributions, and thematic evolution.ResultsResults reveal a rapid rise in research since 2012, with peaks in 2022 and 2024. China leads in publication volume, whereas the United States dominates in total and average citations, reflecting greater academic influence. The University of the Chinese Academy of Sciences and Beijing Normal University emerge as leading institutions. Collaboration networks highlight four major international clusters, with China and the United States at the core. Keyword co-occurrence analysis identifies central topics such as “climate change,” “spring phenology,” “NDVI,” and “remote sensing,” while new themes emerging after 2017 include “urban vegetation phenology,” “grassland ecosystems,” and “extreme climate events.” Thematic evolution indicates a shift from foundational topics such as “MODIS” and “plant growth” toward more integrated themes such as “climate impacts,” “phenological modeling,” and “ecosystem responses.” Co-citation analysis identifies 13 research clusters, including “temperate forest phenology,” “winter wheat,” and “urban spring vegetation phenology.” Recent clusters emphasize high-resolution data sources and urbanization effects, reflecting a transition toward finer-scale and application-oriented research.DiscussionInfluential works by Richardson, Piao, and others form the intellectual foundation of the field and continue to shape its development. Overall, this study provides a comprehensive overview of the evolution and trajectory of vegetation phenology research under climate change. The findings underscore the growing integration of interdisciplinary approaches, finer-scale observations, and an increasing focus on climate-vegetation feedbacks, offering guidance for future research and strategies to enhance ecosystem adaptation.